Development of a Website-Based Learning management system (LMS) at SMAN 52 Jakarta - Abdillah, Maldini; Indiyah, Fariani Hermin; Makmuri (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2024)
The use of information technology in various fields is increasingly developing, one of which is in the field of education. SMAN 52 Jakarta is one of the public high schools in the Cilincing area, North Jakarta, that wants to utilize information technology in the school environment. Researchers conducted surveys and interviews, resulting in 66% of the SMAN 52 community expressing a desire for a website-based learning information system. Based on the interviews, this system is desired to provide a one-stop medium for learning and to ensure the neatness of note-taking in the learning process. Therefore, the researchers designed a Learning Management System (LMS) that manages teacher and student data, as well as supports learning activities such as uploading and downloading learning materials, grading, and discussions. The researchers used the Software Development Life Cycle (SDLC) with a prototype method in their work. This method was chosen for its ease in accommodating changes during the development process. The prototype method was employed with three iterations to serve as a means for evaluation during system development. Using Codeigniter 4 as the framework and PHP as the programming language, the system was developed. The researchers used phpMyAdmin to manage the database. For system testing, they used black box testing with a Likert scale for the entire system, obtaining a score of 96.8% for functionality testing and 96.3% for non-functionality testing. Therefore, it can be concluded that the developed system is highly suitable for use